The effects of feed nitrogen and polyphenol levels on the fate of ingested nitrogen in steers and their implications for nitrogen cycling in mixed farming systems - Delve, Robert J.; Tanner, J.C.; Kimani, S.; Giller, Kenneth E.; Cadisch, Georg; Thorne, Peter J. (British Society of Animal Science, 1998)
Due to inadequate feed supplies for livestock production, farmers throughout the tropics and sub-tropics are being encouraged to supplement low quality basal diets with leguminous forage and concentrates. The varying quality (e.g. nitrogen, lignin and polyphenol content) of these diets will influence feed digestibility, partitioning of nutrients to ruminant tissues and partitioning of nitrogen between urine and faeces. Many reviews have been conducted on the nutritive value of legume species for livestock production (e.g. Lowry et al, 1996) and the classification of the polyphenols they contain (e.g. Reed, 1986). However, the links between diet quality, faecal composition and in particular, the value of excreta in providing nutrients to the soil and hence supporting crop production, are poorly understood.